2008
DOI: 10.1109/csmr.2008.4493312
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Support of ER and UML Class Diagrams during Maintenance Activities on Data Models

Abstract: We present the results of two controlled experiments carried out to compare the support given by the ER and UML class diagrams during the maintenance of data models. The experiments involved Master and Bachelor students performing maintenance tasks on data models represented by ER and UML class diagrams. The results reveal that the two notations give in general the same support. In particular, the correctness level achieved by a subject performing the task on data model represented by an ER diagram are compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Recently, we compared ER and UML class diagrams from a maintainer perspective (De Lucia et al 2008b, c). In particular, in De Lucia et al (2008c) we reported the results of a controlled experiment and a replication aimed at analysing whether UML class diagrams are more comprehensible than ER diagrams.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Recently, we compared ER and UML class diagrams from a maintainer perspective (De Lucia et al 2008b, c). In particular, in De Lucia et al (2008c) we reported the results of a controlled experiment and a replication aimed at analysing whether UML class diagrams are more comprehensible than ER diagrams.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, nowadays ER remains the most used notation to model databases and in some cases it complements UML in the design of software systems. In a recent small industrial survey carried out with our industrial we found that 4 of 13 contacted software companies usually employ both ER and UML class diagrams to represent the same database (De Lucia et al 2008b). Clearly, this can be a problem during the evolution of the data models since more effort is required to maintain the models and their implementation up-to-date.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations